Test and treat approach for tuberculosis infection amongst household contacts of drug-susceptible pulmonary tuberculosis, Mumbai, India - Shah, Daksha; Bhide, Sampada; Deshmukh, Rajesh; Smith, Jonathan P.; Kaiplyawar, Satish; Puri, Varsha; Yeldandi, Vijay; Date, Anand; Nyendak, Melissa; Ho, Christine S.; Moonan, Patrick K. (Frontiers in Tuberculosis, 2024)
Background: Mumbai is one of the most densely populated areas in the world and is a major contributor to the tuberculosis (TB) epidemic in India. A test and treat approach for TB infection (TBI) amongst household contacts (HHC) is part of the national policy for TB preventive treatment (TPT).However, in practice, tests for infection are limited, and prevalence of TBI in Mumbai is not known.We conducted a cross-sectional study among HHCs exposed to persons with microbiologically-confirmed, drug-susceptible pulmonary TB that were notified for antituberculosis treatment in Mumbai, India during September-December, 2021. Community-based field workers made home visits and offered IGRA (QuantiFERON-TB ® Gold In-Tube Plus) tests to HHC aged >5 years. After ruling out active TB disease, HHC with IGRA-positive test results were referred for TPT. All HHC were monitored for at least 24 months. Results: Among 502 HHCs tested, 273 (54%) had IGRA-positive results. A total of 254 (93%) were classified as TBI and were eligible for TPT, of which 215 (85%) initiated TPT, and 194 (90%) completed TPT. In all, 22 HHCs (4%;22/558) were diagnosed with TB disease; of these, five HHC were diagnosed during follow up, of which three were IGRA positive and had no evidence of disease at initial screening but chose not to initiate TPT. A test and treat strategy for HHC resulted in the detection of a substantial proportion of TBI and secondary TB cases. Home-based IGRA testing led to high participation rates, clinical evaluations, TPT initiation, and early diagnoses of additional secondary cases.